Archaeological prospection of a specialized cooking‐pit site at Lunde in Vestfold, Norway. Issue 1 (24th September 2017) - Gustavsen, Lars; Cannell, Rebecca J.S.; Nau, Erich; Tonning, Christer; Trinks, Immo; Kristiansen, Monica; Gabler, Manuel; Paasche, Knut; Gansum, Terje; Hinterleitner, Alois; Poscetti, Valeria; Neubauer, Wolfgang
Abstract: In September 2010, an exceptionally large cooking‐pit site was discovered by means of geophysical prospection at Lunde in Vestfold County, Norway. The site contains in excess of 1000 cooking‐pits and is, to date, one of the largest of its kind discovered in Scandinavia. Features known as cooking‐pits are ubiquitous on Northern European archaeological sites. Despite research spanning decades, however, the true function and role of this rather non‐descript feature type is still debated. Using the results from geophysical prospection, soil analysis, ground‐truthing and excavation, this article aims to better understand this phenomenon by evaluating the physical properties revealed from the data, and setting this exceptional site in a wider cultural‐historical context. The wider, landscape context is accessible from the large‐scale, high‐resolution, landscape archaeological prospection case‐study approach conducted by Ludwig Boltzmann Institute for Archaeological Prospection and Virtual Archaeology (LBI ArchPro). The results suggest that the multi‐method approach is essential in such cases, as it is able to challenge the assumptions of the blanket interpretations often applied, and put the site in a cultural and environmental context.